Integrated model and system for passive houses multiple criteria analysis - Kaklauskas, Artūras; Rutė , Jevgenija; Gudauskas, Renaldas; Banaitis , Audrius (International Journal of Strategic Property Management, 2011)
In order to design and implement a high-quality passive house project, it is neces sary to take care of its efficiency from the brief stage to the end of its life’s service. The entire process should be planned and executed with a consideration of the goals that are aspired to by the participating and interested parties and the micro, meso and macro environment levels. In order to realize the above purposes, an original Model for an Integrated analysis of Passive Houses and Passive Houses Design Multiple Criteria Decision Support System was developedby the authors, enabling one to analyze a passive house’s life cycle, the parties involved in the project and its micro, meso and macro environment as one integrated entity. First Publish Online: 14 Apr 2011